22. Acute ischemic stroke in a patient taking Dabigatran that was neutralized by idarucizumab before fibrinolysis: The first clinically successful case in Vietnam - Ton, Mai Duy; Dung, Nguyen Tien; Phuong, Dao Viet (Tạp chí Nghiên cứu Y học, 2023)
Non-vitamin K antagonist oral anticoagulants are used more and more popularly because they are more effective than vitamin K antagonists. Dabigatran is the only non–vitamin K antagonist oral anticoagulant with an antidote, idarucizumab, in Vietnam. The rate of ischemic stroke while using Dabigatran annually is very rare, only 1.75%. We present the first clinical case in Vietnam using Dabigatran with acute ischemic stroke; patient is a 58 years old female, with history of atrial fibrillation, pacemaker, hypertension, old ischemic stroke, using Dabigatran 150mg, 2 tablets/day. The patient was admitted to the Bach Mai Hospital because of weakness on the right side of the body at the 3rd hour, NIHSS of 10 points, CT scans confirmed acute ischemic stroke due to occlusion of the left M3 segment, the last dose of dabigatran was taken 6 hours prior. The patient was given 2 jars of idarucizumab 2.5g, then rt-PA at a dose of 0.6 mg/kg. The patient improved, the NIHSS score was 3 points, and there was no bleeding in the control CT scan. The patient was discharged after 4 days of treatment, with an mRS score of 1.